1998
DOI: 10.1152/jappl.1998.85.6.2205
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hyperthermia on contraction and dilatation of rabbit femoral arteries

Abstract: To analyze the effect of hyperthermia on the vascular response, the isometric response of isolated rabbit femoral artery segments was recorded at 37 degreesC and hyperthermia (41 and 44 degreesC). Contraction to potassium (5 x 10(-3)-5 x 10(-2) M) was significantly greater at 41 and 44 than at 37 degreesC and increased by inhibition of nitric oxide (NO) synthesis with Nomega-nitro-L-arginine (L-NNA; 10(-4) M) or endothelium removal at 37 degreesC but not at 41 or 44 degreesC. Norepinephrine (10(-9)-10(-4) M) p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
17
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 21 publications
5
17
0
Order By: Relevance
“…The umbilical artery and vein vessels may belong to aberrant cutaneous vessels [31]. Furthermore, in different studies [7,8], it is reported that the effects of warming may be agent-specific; in our study, we observed the same results with 5-HT and ACh. On the other hand, there are conflicting reports about the contractile responses during cooling, because of the use of agents and tissues in noncutaneous vessels.…”
Section: Discussionsupporting
confidence: 84%
“…The umbilical artery and vein vessels may belong to aberrant cutaneous vessels [31]. Furthermore, in different studies [7,8], it is reported that the effects of warming may be agent-specific; in our study, we observed the same results with 5-HT and ACh. On the other hand, there are conflicting reports about the contractile responses during cooling, because of the use of agents and tissues in noncutaneous vessels.…”
Section: Discussionsupporting
confidence: 84%
“…The significant relationship implying a role of local hyperthermia upon limb microcirculatory control is consistent with reports from human forearm (5,6,19) and leg studies (24), showing that increases in local tissue temperature are tightly related to forearm and leg vasodilatation. However, the results from studies in isolated vessel preparations are equivocal with some reports showing an altered vascular responsiveness to elevations in temperature (23), while others do not (31). An alternative possibility is that local hyperthermia acted indirectly upon vasodilatation and sympatholysis through increases in intravascular ATP and/or other vascular signals sensitive to temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Massett et al [19] reported that, during warming the endothelium did not significantly alter the contractile responses to potassium chloride (KCl) and phenylephrine in rings from the mesenteric artery, however only KCl‐induced contractions were potentiated in endothelium‐denuded rings from the thoracic aorta. Moreover, it is reported that during warming, inhibition of nitric oxide synthesis did not modify the increased contraction to potassium, endothelin‐1 and norepinephrine, thus suggesting that the response to these vasoconstrictors is not modulated by nitric oxide during warming [18].…”
Section: Introductionmentioning
confidence: 99%